Penanganan masalah stress kerja pada kasus kesehatan kerja dan penyakit akibat kerja - Monalisa, Agathista Ester; Nugroho, Amanda Permadi Putri; La Base, Dinda Mariella; Kurniawan, Vania Rahma (Institute for Advanced Science, Social, and Sustainable Future, 2024)
Job stress is a problem that often occurs in the modern workplace. This is caused by several factors, such as high work demands, an imbalance between work and personal life, a lack of social support, and job uncertainty. Work stress can have a negative impact on employees' physical and mental well-being, causing various kinds of health problems and decreased productivity. Therefore, it is important for companies and individuals to manage work stress appropriately. One of the causes of work stress is psychosocial danger in the workplace, which includes interactions between work tasks, work design, and the organizational environment, which can influence the physical, psychological, and behavioral conditions of employees. For this reason, work stress management strategies can be implemented by determining healthy working hours, promoting social support in the workplace, and providing stress management training for employees. With proper management, it is hoped that a healthier and more productive work environment can be created.